QseC Mediates Osmotic Stress Resistance and Biofilm Formation in Haemophilus parasuis - He, Lvqin; Dai, Ke; Wen, Xintian; Ding, Lingqiang; Cao, Sanjie; Huang, Xiaobo; Wu, Rui; Zhao, Qin; Huang, Yong; Yan, Qigui; Ma, Xiaoping; Han, Xinfeng; et al. (Frontiers in Microbiology, 2018)
Haemophilus parasuis is known as a commensal organism discovered in the upper respiratory tract of swine where the pathogenic bacteria survive in various adverse environmental stress. QseC, a histidine protein kinase of the two-component regulatory systems CheY/QseC, is involved in the environmental adaptation in bacteria. To investigate the role of QseC in coping with the adverse environment stresses and survive in the host, we constructed a qseC mutant of H. parasuis serovar 13 strain (ΔqseC), MY1902. In this study, we found that QseC was involved in stress tolerance of H. parasuis, by the ΔqseC exhibited a decreased resistance to osmotic pressure, oxidative stress, and heat shock. Moreover, the ΔqseC weakened the ability to take up iron and biofilm formation. We also found that the QseC participate in sensing the epinephrine in environment to regulate the density of H. parasuis.